Influence of an inverter based DG on a double-ended fault location scheme - Jahangar, Hayder; Thomas, David W.P.; Sumner, M.; Rose, Christopher James (2018)
This paper describes the influence of Distributed Generation (DG) on a double ended fault location based on measuring the high frequency fault transients. The additional non-fundamental frequency current components from DG will influence the accuracy of an impedance based fault location technique based on non-fundamental frequencies. A double-ended impedance based fault location technique that utilizes the high frequency content (up to 5 kHz) is studied. The study showed that double-ended method is still able to locate a fault with a maximum error of 4% compared to the case without DG which showed a percentage error up to 2%.